DESCRIPTIVE INDICATORS OF THE LEVEL OF INCOME OF BANKS' ASSETS (Journal of Universal Science Research, 2024)
Economists have proposed a number of indicators describing the income base of commercial banks' assets. However, in our opinion, the system of indicators proposed by the IMF for the purpose of assessing the financial stability of commercial banks, which includes 24 financial indicators, has a unique and important value.